Microbubble dissolution in a multigas environment - Kwan, JJ; Borden, MA (American Chemical Society, 2010)
Microbubbles occur naturally in the oceans and are used in many industrial and biomedical applications. Here, a theoretical and experimental study was undertaken to determine the fate of a microbubble suddenly suspended in a medium with several gas species as in, for example, the injection of an ultrasound contrast agent into the bloodstream. The model expands on Epstein and Plesset’s analysis to include any number of gases. An experimental system was developed which isolates the microbubble in a permeable hollow fiber submerged in a perfusion chamber, allowing rapid exchange of the external aqueous medium. Experimental verification of the model was performed with individual sulfur hexafluoride (SF6) microbubbles coated with the soluble surfactant, sodium dodecyl sulfate (SDS). SDS-coated microbubbles suddenly placed in an air-saturated medium initially grew with the influx of O2 and N2 and then dissolved under Laplace pressure. SF6-filled microbubbles coated with the highly insoluble lipid, dibehenoylphosphatidylcholine, were found to exhibit significantly different behavior owing to a dynamic surface tension. The initial growth phase was diminished, possibly owing to a shell “breakup” tension that exceeded the pure gas/liquid surface tension. Three dissolution regimes were observed: (1) an initial rapid dissolution to the initial diameter followed by (2) steady dissolution with monolayer collapse and finally (3) stabilization below 10 μm diameter. Results indicated that the lipid shell becomes increasingly rigid as the microbubble dissolves, which has important implications on microbubble size distribution, stability, and acoustic properties.